Using QKD in MACsec for secure Ethernet networks. Issue 3 (16th April 2021) - Cho, Joo Yeon; Sergeev, Andrew
Abstract: Media access control security (MACsec) is an IEEE 802.1AE standard for secure communication on Ethernet links. MACsec ensures the confidentiality, integrity and origin authenticity of Ethernet frames. The secrecy of MACsec stems from a root key that is either configured as a pre‐shared key or derived from a mutual authentication protocol. However, both methods are not ideal because such a root key may be disclosed due to human errors or broken by quantum attacks. Here, the authors investigate the quantum key distribution (QKD) as an alternative source of trust for MACsec. QKD can be used as either a root key provider or a session key generator. The authors develop a new key exchange protocol based on QKD for Ethernet networks. Furthermore, it is verified by the experiment that QKD could be well integrated into MACsec without performance degradation.